1981
DOI: 10.1142/s0192415x81000299
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Phenomenon of Latent Propagated Sensation Along the Channels I:

Abstract: By combining electrical impulse stimuli with mechanical ones, we are able to trace out a new line of feeling, coincident with the classical channel course. Impulse stimulation was carried out at the Jing point of the Large Intestine or Stomach channel, namely Shangyan or Lidui. With a small rubber nipple, light taps were applied on the skin along the lines perpendicular to the channel and crossing over the acupuncture points; a specific propagational numb feeling at the points of the channel could be found. By… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…This method can be used to compare PSC lines (i.e., sensation mean courses) to any other data, whose spatial pattern can be mapped on a body scheme similar to that used in our study (Supplementary Figure 1), which constitutes an important step forward in the study of the still unknown physiological basis of PSC and its relation to other acupuncture effects. In our study, PSC lines were compared to classical meridians, as this connection has been reported numerous times before [28]. Despite the purely descriptive character of our analysis, we believe that an average distance between sensation mean courses and meridians of around 1 cm, as observed in our study, clearly points towards a close connection of the two entities.…”
Section: Discussionsupporting
confidence: 65%
“…This method can be used to compare PSC lines (i.e., sensation mean courses) to any other data, whose spatial pattern can be mapped on a body scheme similar to that used in our study (Supplementary Figure 1), which constitutes an important step forward in the study of the still unknown physiological basis of PSC and its relation to other acupuncture effects. In our study, PSC lines were compared to classical meridians, as this connection has been reported numerous times before [28]. Despite the purely descriptive character of our analysis, we believe that an average distance between sensation mean courses and meridians of around 1 cm, as observed in our study, clearly points towards a close connection of the two entities.…”
Section: Discussionsupporting
confidence: 65%
“…Furthermore, there is a latent form of PSC elicited by electrical stimulation of acupuncture points that follows the same patterns as prominent PSC but only emerges when the skin is additionally stimulated by slight tapping with a hammer [72,80]. Finally, Xue has shown that PSC can be felt by acquired amputees in the region of the phantom limb (Figure 3(a)) [69], a finding later replicated by Katz and colleagues [26,82], who reported the induction of phantom limb sensations using TENS of the outer ear.…”
Section: Linear Areal and Mixed Sensationsmentioning
confidence: 92%
“…published in the form of English language scientific papers [69,72,[76][77][78][79][80] with the rest being inaccessible to Western scientists (for a review, see [81]). Furthermore, the methodology of many of the Chinese PSC studies (as judged from the available information) leaves much to be desired.…”
Section: Linear Areal and Mixed Sensationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Acupuncture is defined as the insertion of needles into the body at specific points, and the sensations produced can be local or remote from the site of stimulation (Zhu et al, 1981 ; Chae et al, 2013 ). A number of acupuncture sensation questionnaires focus on the assessment of sensory qualities and the intensity of sensation during acupuncture stimulation (Kong et al, 2007 ; White et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%